Optimization of costs of logistics activities of the enterprise - Yan, Huang (Харківський національний автомобільно-дорожній університет, 2024)
The article defines the essence, structure and classification of logistics costs of enterprise; studies the mechanism of management of logistics costs at a manufacturing enterprise; studies ways to optimize the logistics costs of a manufacturing enterprise; provides an organizational and economic characteristic of enterprise; analyzes the logistics costs of enterprise; studies the system of management of logistics costs at enterprise; defines managerial aspects of optimization of logistics costs at enterprise; substantiates the use of information system for.
Keywords: risk; uncertainty; system; risk management; risk management mechanism